Pengawasan Rutin oleh Praktisi Akuntansi terhadap Bank Berbasis Syariah - Al-Ghifari, Abu Dzar; Saparuddin Siregar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Sharia audit in Islamic banks aims to verify the compliance of these banks with Sharia principles and good governance. Sharia auditors need to have a comprehensive understanding of Sharia principles and relevant Sharia audit standards. They are required to collect sufficient and relevant evidence to support their audit conclusions, evaluate the collected evidence to ensure the compliance of Islamic banks with Sharia principles and good governance, and communicate the audit results to stakeholders. The implementation of Sharia audit standards in Islamic banks involves selecting adequate Sharia auditors, careful planning of Sharia audits, meticulous execution of Sharia audits, clear and transparent reporting of Sharia audit results, and effective follow-up on Sharia audit results. Competencies required by Sharia auditors include knowledge of Islamic law, fiqh muamalah, skills in accounting and auditing, and special characteristics as Sharia auditors.